Transcranial direct current stimulation in the management of epilepsy: a meta-analysis and systematic review - Chen, Yujie; Ou, Zhujing; Hao, Nanya; Zhang, Hesheng; Zhang, Enhui; Zhou, Dong; Wu, Xintong (Frontiers in Neurology, 2024)
Background: Transcranial direct current stimulation (tDCS) has recently become a novel and non-invasive treatment option for refractory epilepsy. Previous systematic reviews have suggested that tDCS may be effective in treating epilepsy, this study presents the first meta-analysis on its effectiveness.We searched PubMed, Embase, Cochrane Library, and Web of Science for relevant randomized controlled trials (RCTs) from database inception to May 2024. The Cochrane risk of bias tool RoB2.0 was used to assess the risk of bias. Primary outcomes included changes in seizure frequency from baseline and the proportion of patients with a ≥50% reduction in seizure frequency.Of the 608 studies initially identified, 14 were finally included. The pooled results from the random-effects model indicated that tDCS significantly reduced seizure frequency (WMD 0.41, 95%CI 0.24, 0.59). Further subgroup analysis revealed that tDCS significantly reduced seizure frequency in temporal lobe epilepsy, and seizure frequency was more alleviated in studies that had treatment sessions of fewer than 5 times, and followed up within 2 months' post-treatment. Only four studies provided data on patients with a ≥50% reduction in seizure frequency, showing no significant difference (RR 2.96, 95%CI 0.85,10.32). In the systematic review, three studies analyzed cognitive function changes after tDCS treatment, but none reported significant improvements. The most common side effect during tDCS treatment was transient tingling, and no patients required additional life-support measures due to side effects.The current meta-analysis on available trials indicates that tDCS can effectively reduce seizure frequency in the short term and is well tolerated. However, its impact on cognitive improvement in epilepsy patients requires further investigation.